Synthesis process of high-purity silicon carbide ceramic catalyst

CN119869578APending Publication Date: 2025-04-25ZIBO SHENGYE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510075978.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing silicon carbide ceramic catalysts have problems such as large particle size, many impurities, long process cycles and easy to produce closed inner pores, which seriously restricts their application in engineering.

Method used

A process is adopted, including ball milling and sieving to obtain a silicon carbide ceramic powder, followed by adding cerium acetate to deionized water and soaking, followed by soaking in palladium nitrate solution and blow-drying and calcining in sections to obtain a high purity silicon carbide ceramic catalyst.

Benefits of technology

The catalyst particle size is uniform, the purity is high, the production process is simple, and the CO2 methanation catalytic efficiency is significantly improved, reducing the cost of CO2 reuse.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of synthesis of ceramic catalysts, in particular to a synthesis process of a high-purity silicon carbide ceramic catalyst. The process comprises the following production steps: ball-milling silicon carbide ceramic; modifying and drying the silicon carbide ceramic powder; diluting a palladium nitrate solution; soaking the silicon carbide ceramic powder into the palladium nitrate solution; and carrying out forced air drying and calcining to obtain the high-purity silicon carbide ceramic catalyst. According to the process, the loading capacity of the silicon carbide ceramic is enhanced, the operation steps are simple and convenient, the production efficiency is high, and the obtained catalyst obviously improves the catalytic efficiency of CO2 methanation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic catalyst synthesis, and in particular to a synthesis process of a high-purity silicon carbide ceramic catalyst. Background Art

[0002] Silicon carbide, also known as corundum, is a covalent compound composed of silicon atoms and carbon atoms. It has attracted attention for its corrosion resistance, wear resistance, high temperature resistance, oxidation resistance, high strength and high hardness, and is widely used in abrasives, ceramics, refractories and metallurgy. Silicon carbide has more than 200 crystal forms under different physical and chemical conditions. Based on this characteristic, silicon carbide has a wide range of optical, electronic and thermal properties. The main methods for synthesizing silicon carbide reported so far are mechanical alloying, carbon thermal reduction, sol-gel and chemical vapor deposition. In addition, there are radio frequency thermal plasma, in-situ catalysis, microwave and mesoporous template methods.

[0003] Silicon carbide ceramics are ceramics with silicon carbide as the main component. They are particularly well-used in composite materials, catalysts, fluorescent biomarkers, bioadhesives, microwave absorption, and supercapacitors. Silicon carbide ceramics' unique optoelectronic properties, low thermal expansion, and good chemical and thermal stability make them ideal inert solids in catalysis. As silicon carbide ceramic catalysts are increasingly used in related fields, the requirements for the purity, particle size, and morphology of silicon carbide ceramic catalysts are becoming increasingly higher. The silicon carbide ceramic catalysts currently produced still have problems such as large particle size, many impurities, long process cycles, and easy generation of closed internal pores, which seriously restricts the application of silicon carbide ceramics in engineering. Therefore, the production process of high-purity silicon carbide ceramic catalysts is still a topic worth exploring. Summary of the invention

[0004] In view of the problems existing in the background technology, the present invention provides a synthesis process of a high-purity silicon carbide ceramic catalyst. The obtained catalyst has uniform particle size, high purity, and simple production process operation, and comprises the following steps:

[0005] Step a: ball-milling silicon carbide ceramics and sieving to obtain silicon carbide ceramic powder;

[0006] Step b: adding silicon carbide ceramic powder to a small amount of deionized water, then dropping cerium acetate therein, soaking for 2 to 3 hours, taking out, and drying;

[0007] Step c: ultrasonically treating the ammonia water for half an hour, and then adding palladium nitrate dropwise thereto to obtain a diluted palladium nitrate solution;

[0008] Step d: soaking the dried silicon carbide ceramic powder in the palladium nitrate solution obtained in step c for 2 to 3 hours, and then taking it out;

[0009] Step e: drying the soaked silicon carbide ceramic powder by forced air at 120° C. for 3 to 4 hours;

[0010] Step f: calcining the dried silicon carbide ceramic powder in stages at elevated temperatures for 5 to 6 hours, and taking it out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0011] Preferably, the ball milling conditions in step a are: under the condition of ball: material = 1:1, the ball milling speed is set to 350 rpm, and the grinding is carried out for 18 to 24 hours.

[0012] Preferably, the particle size of the silicon carbide ceramic powder obtained by sieving in step a is 1 to 15 nm.

[0013] Preferably, the specific implementation method of step b is: adding silicon carbide ceramic powder to an equal volume of deionized water, ultrasonically mixing for 10 minutes, then dropping an equal amount of cerium acetate solution thereto, soaking for 2 to 3 hours under stirring at room temperature, and then filtering and drying.

[0014] Further preferably, the drying condition is to place the silicon carbide ceramic powder in a vacuum drying oven at 100° C. and dry it for 12 hours.

[0015] Preferably, the concentration of the palladium nitrate solution obtained in step c is 10 to 35 wt %.

[0016] Preferably, the soaking condition of step d is soaking in a water bath at 100°C.

[0017] Preferably, the calcination in step f is as follows: placing the silicon carbide ceramic in a vacuum tube furnace for calcination under nitrogen conditions, setting the calcination temperature of the first stage to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcining for 1-1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcining for 1-2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, and calcining for 0.5-1 hour.

[0018] A synthesis process for a high-purity silicon carbide ceramic catalyst. The purity of the obtained silicon carbide ceramic catalyst is greater than 98%.

[0019] Compared with the existing technology, the present invention has the following technical advantages:

[0020] Silicon carbide ceramics have unique physical and chemical properties, namely good thermal conductivity, strong anti-oxidation performance and high mechanical strength, and thus become a new type of industrial catalyst carrier. The present invention uses silicon carbide ceramics as a catalyst carrier, breaking through the limitations of cost and performance and achieving stable multifunctional catalysis.

[0021] In daily production and life, a large amount of greenhouse gas CO2 is produced, which will cause damage to the natural environment. With the help of catalysts, CO2 can be methanized, which is beneficial to ecological balance and social sustainable development. The specific surface area of ​​the catalyst obtained by the present invention is 60 to 100 m 2 / g, the palladium loading is 3-8wt%, which is significantly higher than the existing technology. The obtained catalyst has uniform particle size of (5.0±1.0)nm, small and concentrated particle size, and purity greater than 98%. In addition, the production process is simple to operate, and a slight change in the production process conditions has no significant effect on the performance of the catalyst product. It can also significantly improve the catalytic efficiency of CO2 methanation and reduce the cost of CO2 recycling. DETAILED DESCRIPTION

[0022] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0023] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0024] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0025] Embodiment 1;

[0026] The silicon carbide ceramic powder was ground at a ball mill speed of 350 rpm for 18 hours under the condition of ball: material = 1:1, and then sieved to obtain silicon carbide ceramic powder with a particle size of 1 to 15 nm; then the silicon carbide ceramic powder was added to an equal volume of deionized water, ultrasonically mixed for 10 minutes, and then an equal amount of cerium acetate solution was added thereto, and the mixture was soaked for 3 hours under stirring at room temperature and filtered. The silicon carbide ceramic powder was placed in a vacuum drying oven at 100° C. and dried for 12 hours for standby use. The ammonia water is ultrasonicated for half an hour, and then palladium nitrate is added dropwise thereto to obtain a palladium nitrate solution with a concentration of 12wt% after dilution; the dried silicon carbide ceramic powder is immersed in the palladium nitrate solution obtained in step c, immersed in a water bath at 100°C for 2 hours, and then taken out; air-dried at 120°C for 4 hours; the dried silicon carbide ceramic powder is placed in a vacuum tube furnace for calcination under nitrogen conditions, and the calcination temperature of the first stage is set to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcined for 1 hour; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcined for 1 hour; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, calcined for 0.5 hour, and taken out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0027] Embodiment 2:

[0028] The silicon carbide ceramic was ground at a ball mill speed of 350 rpm for 20 hours under the condition of ball: material = 1:1, and then sieved to obtain silicon carbide ceramic powder with a particle size of 1 to 15 nm; then the silicon carbide ceramic powder was added to an equal volume of deionized water, ultrasonically mixed for 10 minutes, and then an equal amount of cerium acetate solution was added thereto, and the mixture was soaked for 3 hours under stirring at room temperature and filtered. The silicon carbide ceramic powder was placed in a vacuum drying oven at 100° C. and dried for 12 hours for standby use. The ammonia water is ultrasonicated for half an hour, and then palladium nitrate is added dropwise thereto to obtain a palladium nitrate solution with a concentration of 20wt% after dilution; the dried silicon carbide ceramic powder is immersed in the palladium nitrate solution obtained in step c, immersed in a water bath at 100°C for 2 hours, and then taken out; air-dried at 120°C for 4 hours; the dried silicon carbide ceramic powder is placed in a vacuum tube furnace for calcination under nitrogen conditions, and the calcination temperature of the first stage is set to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcined for 1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcined for 2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, calcined for 1 hour, and taken out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0029] Embodiment three;

[0030] The silicon carbide ceramic was ground at a ball mill speed of 350 rpm for 18 hours under the condition of ball: material = 1:1, and then sieved to obtain silicon carbide ceramic powder with a particle size of 1 to 15 nm; then the silicon carbide ceramic powder was added to an equal volume of deionized water, ultrasonically mixed for 10 minutes, and then an equal amount of cerium acetate solution was added thereto, and the mixture was soaked for 2.5 hours under stirring at room temperature and filtered. The silicon carbide ceramic powder was placed in a vacuum drying oven at 100° C. and dried for 12 hours for standby use. The ammonia water is ultrasonicated for half an hour, and then palladium nitrate is added dropwise thereto to obtain a palladium nitrate solution with a concentration of 25wt% after dilution; the dried silicon carbide ceramic powder is immersed in the palladium nitrate solution obtained in step c, immersed in a water bath at 100°C for 3 hours, and then taken out; air-dried at 120°C for 4 hours; the dried silicon carbide ceramic powder is placed in a vacuum tube furnace for calcination under nitrogen conditions, and the calcination temperature of the first stage is set to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcined for 1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcined for 2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, calcined for 1 hour, and taken out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0031] Embodiment 4:

[0032] The silicon carbide ceramic was ground at a ball mill speed of 350 rpm for 24 hours under the condition of ball: material = 1:1, and then sieved to obtain silicon carbide ceramic powder with a particle size of 1 to 15 nm; then the silicon carbide ceramic powder was added to an equal volume of deionized water, ultrasonically mixed for 10 minutes, and then an equal amount of cerium acetate solution was added thereto, and the mixture was soaked for 2 hours under stirring at room temperature and filtered. The silicon carbide ceramic powder was placed in a vacuum drying oven at 100° C. and dried for 12 hours for standby use. The ammonia water is ultrasonicated for half an hour, and then palladium nitrate is added dropwise thereto to obtain a palladium nitrate solution with a concentration of 30wt% after dilution; the dried silicon carbide ceramic powder is immersed in the palladium nitrate solution obtained in step c, immersed in a water bath at 100°C for 2 hours, and then taken out; air-dried at 120°C for 4 hours; the dried silicon carbide ceramic powder is placed in a vacuum tube furnace for calcination under nitrogen conditions, and the calcination temperature of the first stage is set to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcined for 1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcined for 2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, calcined for 1 hour, and taken out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0033] Embodiment five;

[0034] The silicon carbide ceramic was ground at a ball mill speed of 350 rpm for 24 hours under the condition of ball: material = 1:1, and then sieved to obtain silicon carbide ceramic powder with a particle size of 1 to 15 nm; then the silicon carbide ceramic powder was added to an equal volume of deionized water, ultrasonically mixed for 10 minutes, and then an equal amount of cerium acetate solution was added thereto, and the mixture was soaked for 2.5 hours under stirring at room temperature and filtered. The silicon carbide ceramic powder was placed in a vacuum drying oven at 100° C. and dried for 12 hours for standby use. The ammonia water is ultrasonicated for half an hour, and then palladium nitrate is added dropwise thereto to obtain a palladium nitrate solution with a concentration of 35wt% after dilution; the dried silicon carbide ceramic powder is immersed in the palladium nitrate solution obtained in step c, immersed in a water bath at 100°C for 2.5 hours, and then taken out; air-dried at 120°C for 3.5 hours; the dried silicon carbide ceramic powder is placed in a vacuum tube furnace for calcination under nitrogen conditions, and the calcination temperature of the first stage is set to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcined for 1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcined for 2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, calcined for 1 hour, and taken out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

[0035] Performance Testing

[0036] The silicon carbide ceramic catalysts obtained in Examples 1 to 5 were characterized, and the results are shown in Table 1.

[0037] Table 1 Catalyst characterization results

[0038] Serial number <![CDATA[Specific surface area (m 2 / g)]]> Palladium loading (wt%) Average particle size (nm) Embodiment 1 70 3 5.92 Embodiment 2 60 5 5.50 Embodiment 3 70 6 4.38 Embodiment 4 80 8 5.04 Embodiment 5 100 5 4.29

[0039] Catalyst Application

[0040] After the catalyst was activated with hydrogen, a catalytic CO2 methanation experiment was carried out. The results are shown in Table 2.

[0041] Table 2 Experimental results of CO2 methanation conversion rate

[0042] Serial number Conversion Rate % Embodiment 1 65 Embodiment 2 69 Embodiment 3 71 Embodiment 4 70 Embodiment 5 66

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A synthesis process of high-purity silicon carbide ceramic catalyst, characterized in that: The following steps are involved: Step a: ball-milling silicon carbide ceramics and sieving to obtain silicon carbide ceramic powder; Step b: adding silicon carbide ceramic powder to a small amount of deionized water, then dropping cerium acetate therein, soaking for 2 to 3 hours, taking out, and drying; Step c: ultrasonically treating the ammonia water for half an hour, and then adding palladium nitrate dropwise thereto to obtain a diluted palladium nitrate solution; Step d: soaking the dried silicon carbide ceramic powder in the palladium nitrate solution obtained in step c for 2 to 3 hours, and then taking it out; Step e: drying the soaked silicon carbide ceramic powder by forced air at 120° C. for 3 to 4 hours; Step f: calcining the dried silicon carbide ceramic powder in stages at elevated temperatures for 5 to 6 hours, and taking it out after cooling to obtain a high-purity silicon carbide ceramic catalyst.

2. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The ball milling conditions of step a are as follows: under the condition of ball: material = 1:1, the ball milling speed is set to 350 rpm and the grinding is performed for 18 to 24 hours.

3. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The particle size of the silicon carbide ceramic powder obtained by sieving in step a is 1 to 15 nm.

4. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The specific implementation of step b is: adding silicon carbide ceramic powder to an equal volume of deionized water, ultrasonically mixing for 10 minutes, then dropping an equal amount of cerium acetate solution thereto, soaking for 2 to 3 hours under stirring at room temperature, and then filtering and drying.

5. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 4, characterized in that: The drying condition is to place the silicon carbide ceramic powder in a vacuum drying oven at 100° C. and dry it for 12 hours.

6. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The concentration of the palladium nitrate solution obtained in step c is 10-35wt%.

7. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The soaking condition of step d is soaking in a 100° C. water bath.

8. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The calcination in step f is as follows: placing the silicon carbide ceramic in a vacuum tube furnace for calcination under nitrogen conditions, setting the calcination temperature of the first stage to increase from room temperature to 100-250°C at a rate of 5-10°C / min, and calcining for 1-1.5 hours; the calcination temperature of the second stage is increased from 100-250°C to 350-400°C at a rate of 10-15°C / min, and calcining for 1-2 hours; the calcination temperature of the third stage is increased from 350-400°C to 550-650°C at a rate of 10-15°C / min, and calcining for 0.5-1 hour.

9. The synthesis process of a high-purity silicon carbide ceramic catalyst according to claim 1, characterized in that: The purity of the silicon carbide ceramic catalyst is greater than 98%.